2015
DOI: 10.1159/000369458
|View full text |Cite
|
Sign up to set email alerts
|

Premature Adrenarche - A Common Condition with Variable Presentation

Abstract: Adrenarche refers to a maturational increase in the secretion of adrenal androgen precursors, mainly dehydroepiandrosterone (DHEA) and its sulfate (DHEAS). In premature adrenarche (PA), clinical signs of androgen action appear before the age of 8/9 years in girls/boys, concurrently with the circulating DHEA(S) concentrations above the usually low prepubertal level. The most pronounced sign of PA is the appearance of pubic/axillary hair, but also other signs of androgen effect (adult type body odor, acne/comedo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 352 publications
(114 citation statements)
references
References 75 publications
7
100
2
5
Order By: Relevance
“…Подростковый возраст -один из наиболее важ-ных периодов развития человека в связи со слож-ными нейроэндокринными и другими биологическими изменениями, на фоне которых физическое и поло-вое развитие максимально приближается к состоянию взрослого организма [1][2][3]. Физиологический процесс полового созревания продолжается порядка 4-5 лет, однако с учетом различных генетических и молекулярных детерминант сроки могут изменяться, даже при условии однородности факторов внешней среды [1].…”
Section: обоснованиеunclassified
See 2 more Smart Citations
“…Подростковый возраст -один из наиболее важ-ных периодов развития человека в связи со слож-ными нейроэндокринными и другими биологическими изменениями, на фоне которых физическое и поло-вое развитие максимально приближается к состоянию взрослого организма [1][2][3]. Физиологический процесс полового созревания продолжается порядка 4-5 лет, однако с учетом различных генетических и молекулярных детерминант сроки могут изменяться, даже при условии однородности факторов внешней среды [1].…”
Section: обоснованиеunclassified
“…На основании данных крупного эпидемиологиче-ского исследования Third National Health and Nutrition Examination Survey (NHANES III) 2 , выполненного в 2003 г., разработаны нормативы физического и полового раз-вития представителей различных этнических групп севе-роамериканской популяции, которые в настоящее время используются как референтные в большинстве стран мира, включая Россию [5]. С учетом международных регламентирующих документов, определивших критери-ями начала полового созревания 2-ю стадию развития молочных желез у девочек и 2-ю стадию развития наруж-ных половых органов у мальчиков, экспертами NHANES был определен средний возраст начала пубертатного периода: для девочек европеоидной расы -10,4 (10,1-10,7) года, негроидной расы -9,5 (9,1-9,8) года; для юношей -10,0 (9,6-10,4) лет и 9,2 (8,62-9,64) года соот-ветственно [10][11][12].…”
Section: педиатрическая фармакологияunclassified
See 1 more Smart Citation
“…In the past, idiopathic PA was considered a benign condition, a normal variation in the time of puberty. In subsequent studies, however, researchers demonstrated that PA may be a sign of increased risk for metabolic disorders (Oron et al 2012), such as dyslipidemia (Ferran et al 2011) and insulin resistance (IR) (Sopher et al 2011), and also for the development of diabetes mellitus 2 (DM2), (Sopher et al 2011, Utriainen et al 2015) metabolic syndrome (MetS) (Idkowiak et al 2011, Utriainen et al 2015 and polycystic ovary syndrome (PCOS) (Idkowiak et al 2011). …”
Section: Premature Adrenarchementioning
confidence: 99%
“…Premature adrenarche (PA) is diagnosed when early adrenal androgen exposure leads to clinical signs (adult-type body odor, oily hair and skin, comedones/acne, axillary or pubic hair) before the age of 8/9 years in a girl/boy and other causes of hyperandrogenism have been excluded [1, 2]. Children with PA have slightly advanced bone age, and they are typically tall for age and overweight already in early childhood [1].…”
Section: Introductionmentioning
confidence: 99%